Correlation of Tc-99 m ethyl cysteinate dimer single-photon emission computed tomography and clinical presentations in patients with low cobalamin status. Issue 1 (December 2015) - Tu, Min-Chien; Lo, Chung-Ping; Chen, Ching-Yuan; Huang, Ching-Feng
Abstract Background Cobalamin (Cbl) deficiency has been associated with various neuropsychiatric symptoms of different severities. While some studies dedicated in structural neuroimaging credibly address negative impact of low Cbl status, functional imaging reports are limited. We herein retrospectively review the correlation of Tc-99 m ethyl cysteinate dimer single-photon emission computed tomography (Tc-99 m-ECD SPECT) and clinical presentations among patients with low serum cobalamin (Cbl) status (<250 pg/ml). Methods Twelve symptomatic patients with low serum Cbl status were enrolled. Clinical presentations, Tc-99 m-ECD SPECT, and neuropsychological tests were reviewed. Results Dysexecutive syndrome (67 %), forgetfulness (50 %), attention deficits (42 %), and sleep disorders (33 %) constituted the major clinical presentations. All patients (100 %) had temporal hypoperfusion on the Tc-99 m-ECD SPECT. Five patients (42 %) had hypoperfusion restricted within temporal regions and deep nuclei; seven patients (58 %) had additional frontal hypoperfusion. In patients with hypoperfusion restricted within temporal regions and deep nuclei, psychiatric symptoms with spared cognition were their main presentations. Among patients with additional frontal hypoperfusion, six of seven patients (86 %) showed impaired cognitive performances (two of them were diagnosed as having dementia). Among ten patients who finished neuropsychological tests, abstract thinking (70 %) was the most commonly affected, followed by verbal fluency (60 %), short-term memory (50 %), and attention (50 %). Anxiety and sleep problems were the major clinically remarkable psychiatric features (33 % both). Four Tc-99 m-ECD SPECT follow-up studies were available; the degree and extent of signal reversal correlated with cognitive changes after Cbl replacement therapy. Conclusions Our TC-99 m-ECD SPECT observations provide pivotal information of neurobiological changes within basal ganglia and fronto-temporal regions in conjunction with disease severity among patients with Cbl deficiency. Hypoperfusion within thalamus/basal ganglia and temporal regions may be seen in the earlier state of Cbl deficiency, when psychiatric symptoms predominate. Hypoperfusion beyond thalamus/basal ganglia and involving frontal regions appears when cognitive problems, mostly dysexecutive syndrome, are manifested. Symmetric hypofrontality of SPECT in the context of dysexcutive syndrome serves as a distinguishing feature of non-amnestic mild cognitive impairment attributed to Cbl deficiency. Concordant with TC-99 m-ECD SPECT findings, the psychiatric symptoms and dysexcutive syndrome undergird impaired limbic and dorsolateral prefrontal circuits originating from basal ganglia respectively.